Soggetto Istituzione. Freud con Kelsen nella scienza del pensiero di Giacomo B. Contri - Pediconi, Maria Gabriella (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
This article configures the intellectual encounter between three thinkers, Sigmund Freud, Hans Kelsen and Giacomo B. Contri: an encounter that gave rise to an unprecedented concept in the history of thought, the ‘subject as institution’. We will discover a Kelsen who, more Freudian than Freud, corrects him, and a Kelsenian psychoanalyst who renews psychoanalysis through the conception of law: this is the encounter that allowed Giacomo Contri to realise a normative foundation of the subject, an original and unique conception in the psychoanalytic field. In the hope that it would be fruitful for the law itself.